2008
DOI: 10.1097/meg.0b013e32830aba6d
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pathological duodenogastric reflux and the relationship between duodenogastric and duodenogastrooesophageal reflux in chronic gastrooesophageal reflux disease

Abstract: Pathological DGR is present in a little more than a quarter of patients with recurrent reflux and dyspeptic symptoms after PPI therapy. Excessive DGR is not a prerequisite for pathological oesophageal exposure to duodenal contents. Gastric bilirubin monitoring may be useful to choose the best surgical treatment for patients with reflux and dyspeptic symptoms refractory to PPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
4
1
5
Order By: Relevance
“…In our paper, we noticed that duodenogastric reflux is found in 34% of patients with GERD versus 25% mentioned in Brillantino's paper [1].…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…In our paper, we noticed that duodenogastric reflux is found in 34% of patients with GERD versus 25% mentioned in Brillantino's paper [1].…”
Section: Discussioncontrasting
confidence: 47%
“…The duodenogastric reflux was described in about 25% cases of patients with GERD according to the paper of Brillantino A et al [1]. They described duodenogastric reflux associated with gastric ulcer, gallbladder lithiasis and esophagitis and they pointed that the duodenogastric reflux can damage the gastric and esophageal mucosa due to the fact that it contains biliary acids and pancreatic juice [7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, current evidence using the multichannel impedance with pH sensor suggests that weakly acidic events (nadir pH between 4 and 7) in the esophagus are associated with classic GERD symptoms, particularly in patients taking proton pump inhibitors (PPIs) [31, 32]. In addition, studies using bilirubin monitoring together with pH monitoring showed a synergism between acid and bile reflux components in determining esophageal mucosal damage [33, 34]. …”
Section: Pathophysiologymentioning
confidence: 99%
“…В то же время взаимозависимость параметров внутрипищеводного и внутрижелудочного рН, а также моторики верхних отделов пищеварительного тракта натощак и после приема пищи изучена недостаточно. Одним из наименее изученных аспектов проблемы является связь проявлений ГЭРБ, ассоциированной с разными типами рефлюкса в пищевод, и функциональных секреторных и моторно-тонических расстройств пищевода, желудка и двенадцатиперстной кишки (ДПК) [8,9].…”
unclassified